Auditory Processing Deficits in Reading Disabled Adults - Amitay, Sygal (Springer-Verlag, 2002)
The nature of the auditory processing deficit of disabled readers is still an unresolved issue. The quest for a fundamental, nonlinguistic, perceptual impairment has been dominated by the hypothesis that the difficulty lies in processing sequences of stimuli at presentation rates of tens of milliseconds. The present study examined this hypothesis using tasks that require processing of a wide range of stimulus time constants. About a third of the sampled population of disabled readers (classified as "poor auditory processors") had difficulties in most of the tasks tested: detection of frequency differences, detection of tones in narrowband noise, detection of amplitude modulation, detection of the direction of sound sources moving in virtual space, and perception of the lateralized position of tones based on their interaural phase differences. Nevertheless, across-channel integration was intact in these poor auditory processors since comodulation masking release was not reduced. Furthermore, phase locking was presumably intact since binaural masking level differences were normal. In a further examination of temporal processing, participants were asked to discriminate two tones at various intervals where the frequency difference was ten times each individual's frequency just noticeable difference (JND). Under these conditions, poor auditory processors showed no specific difficulty at brief intervals, contrary to predictions under a fast temporal processing deficit assumption. The complementary subgroup of disabled readers who were not poor auditory processors showed some difficulty in this condition when compared with their direct controls. However, they had no difficulty on auditory tasks such as amplitude modulation detection, which presumably taps processing of similar time scales. These two subgroups of disabled readers had similar reading performance but those with a generally poor auditory performance scored lower on some cognitive tests. Taken together, these results suggest that a large portion of disabled readers suffer from diverse difficulties in auditory processing. No parsimonious explanation based on current models of low-level auditory processing can account simultaneously for all these results, though increased within-channel noise is consistent with the majority of the deficits found in the subgroup of poorer auditory processors.